Identifying wheat root traits and regulatory genes for nitrogen uptake efficiency - Griffiths, Marcus (2018)
Wheat (Triticum spp.) is a particularly important crop for food security, providing 20% of worldwide calorie intake. Food production is not meeting the projected global demand of an increase of 2.4% p.a. Improvement of resource capture in wheat could help meet this demand. Nitrogen (N) is an essential macronutrient for plant growth and development; however, nitrogen use efficiency (NUE) for cereal production is only 33%. Domestication of modern varieties of wheat may have lost potentially beneficial agronomic traits, particularly in the root system. Optimisation of root system architecture could profoundly improve nitrogen uptake efficiency (NUpE) and in turn increase the yield potential of the crop. Using ancestral wheat germplasm and mapping populations, desirable traits may be identified and bred back into commercial wheat varieties to increase yield potential. Using a high-throughput hydroponic root phenotyping system, N-dependent root traits have been identified in wheat mapping populations. Using transcriptomic analyses, the gene expression profile of a candidate N-dependent root QTL has been identified. Using a new root phenotyping system, X-ray micro-computed tomography (μCT), a three-dimensional representation of wheat roots can now be imaged in soil. A selection of the same mapping lines have been used for 3D μCT analysis based on field NUpE parameters to identify promising root traits in both seedlings and mature plants.